Pelatihan Penulisan Cerita Lokal Bergenre Magis di Komunitas Sastra Darussalam - Faruk, Faruk; Manshur, Fadlil Munawwar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
The third-year of service activities (2021) at the Komunitas Sastra Darussalam were centered on training in writing local stories of the magical genre. Komunitas Sastra Darussalam has the potential to maximize the pesantren’s cultural background as the basis for their writing, such as through the genre of magical realism which is considered very close to their lives. Through training and mentoring held by the service community team, it is expected that they will ignite their ability to continue developing to compete at the national or global level. In the first year (2019), activities are focused on developing story ideas that produce mini-fictions about life with a pesantren background. In the second year (2020), service participants received training on writing realism genre literary works. So, in the third year (2021), the activities focused on the story’s substance, that is rewriting local stories (folklore) with the magical genre. From this training and mentoring that has been carried out, it was found that the tendency of writing local stories by KSD writers has shown its magical side. The stories explored by the participants were quite diverse, not only tending to explore local stories, but the participants also showed their tendencies as a pesantren community, some of them took stories with a magical substance that developed in Islam. ==== Kegiatan Pengabdian kepada Masyarakat pada tahun ketiga (2021) di Komunitas Sastra Darussalam dipusatkan pada pelatihan penulisan cerita lokal bergenre magis. Komunitas Sastra Darussalam sendiri adalah sebuah kelompok yang berpotensi menumbuhkan penulis-penulis yang dapat memaksimalkan latar budaya pesantren sebagai basis kepenulisan mereka, di antaranya, melalui genre realisme magis yang dianggap sangat dekat dengan kehidupan mereka. Pelatihan dan pendampingan yang diadakan oleh Tim Pengabdian ini diharapkan mampu memantik kemampuan anggota komunitas untuk terus berkembang dan bersaing dalam tataran nasional ataupun global. Jika tahun pertama (2019) kegiatan difokuskan pada pengembangan ide cerita yang menghasilkan fiksi mini mengenai kehidupan berlatar pesantren, tahun kedua (2020) peserta pengabdian mendapat pelatihan mengenai penulisan karya sastra bergenre realisme, dan pada tahun ketiga (2021), kegiatan difokuskan pada substansi cerita, yaitu menulis ulang cerita lokal (cerita rakyat) yang bergenre magis. Dari pelatihan dan pendampingan yang telah dilakukan ditemukan bahwa kencenderungan penulisan cerita lokal oleh penulis-penulis KSD telah menampakkan sisi magisnya. Cerita yang dieksplorasi peserta cukup beragam, tidak hanya cenderung pada eksplorasi cerita-cerita lokal, peserta juga menampakkan kecenderungan mereka sebagai masyarakat pesantren, yaitu sebagian di antara mereka mengambil cerita-cerita bersubstansi magis yang berkembang dalam Islam.